Trend of studies on prenatal care in nursing in Brazil - Karine Eliel Stumm; Carolina Carbonell dos Santos; Lúcia Beatriz Ressel (Universidade Federal de Santa Maria, 2012)
Objective: to identify the trend of Brazilian scientific production related to nursing care in prenatal care. Method: it is an integrative review whose data were collected in "Literatura Latino-Americana e do Caribe em Ciências da Saúde" (LiLACS) electronic database and in the website Scientific Electronic Library Online (SciELO), using the keywords "prenatal care" and "nursing" in July, 2011. Results: the following categories emerged from thematic analysis: quality of prenatal care and nurses' performance in prenatal care assistance. In the analyzed studies, the authors emphasize the importance of standardize the activities of assistance to prenatal, organizing the service in order to improve their quality. Final conclusion: it was noticed a trend in humanistic productions on the subject, emphasizing health education as a propeller of this paradigm and consistent with Policy for Integral Attention to Women's Health